Comparison of Psychological Empowerment and Moral Distress in Male and Female Nurses - Alimohammadi Leilehkouhi, Sima; Foroughi Kaldareh, Zahra (KMAN Counseling & Psychology Nexus, 2025)
The aim of this study was to compare psychological empowerment and moral distress in male and female nurses in District 6 of Tehran. The study population included all nurses working in hospitals in District 6 of Tehran in 2024. Using an exploratory method and referring to similar previous studies, the sample size was determined to be 60 participants (30 female nurses and 30 male nurses), selected through simple random sampling and assigned to the groups. The research instruments included the Spreitzer Psychological Empowerment Questionnaire and the Hamric et al. Moral Distress Questionnaire. The obtained data were analyzed using SPSS version 26 software in two sections: descriptive statistics (measures of dispersion, frequency, and charts) and inferential statistics (multivariate analysis of variance). The results of the statistical analysis indicated that the significance level obtained for psychological empowerment and moral distress in male and female nurses was less than 0.05. Therefore, the research hypothesis was accepted, and the null hypothesis was rejected. Thus, it can be concluded that there is a significant difference in psychological empowerment and moral distress between male and female nurses. Based on the results, there is a significant difference in psychological variables such as psychological empowerment and moral distress between male and female nurses in District 6 of Tehran, which is highly important.